EXPERIENCE OF REGULATING THE SECURITIES MARKET IN FOREIGN COUNTRIES - Turanboyev Boburjon Qodirjon o‘g‘li (Sciental Journals Publishing, 2025)
The regulation of securities markets is a critical component of a stable and efficient global financial system. This article examines the diverse experiences of regulating securities markets in key foreign jurisdictions, including the United States, the United Kingdom, the European Union, and emerging markets like China. The analysis reveals a spectrum of approaches, from the disclosure-based, rules-intensive model of the U.S. to the principles-based, "twin peaks" structure of the U.K. and the harmonized, supranational framework of the EU. The findings indicate a global trend towards enhancing transparency, strengthening investor protection, and managing systemic risk, particularly in the wake of the 2008 financial crisis. However, significant national differences persist, shaped by legal traditions, market maturity, and economic priorities. The article discusses the ongoing challenges posed by financial technology (Fintech), globalization, and the need to balance market innovation with financial stability, concluding that no single regulatory model is universally optimal.